Analisa Pembangkit Pengatur Tegangan Pada Penyulang 20 kV (Aplikasi Gardu Induk PT.PLN (Persero) Sei Rotan) - indra roza (RELE (Rekayasa Elektrikal dan Energi) : Jurnal Teknik Elektro, 2018)
With the rapid power needs of the people living in urban and rural areas will not affect either the quality of the voltage in the value of PLN service under specified standards. Factors affecting namely the existence of the impedance on the channel, there will be a voltage drop, which is the product of current voltage with an impedance of electrical power distribution equipment. The greater the resistance of the conductor of the price, the greater the voltage drop across the electric power system. It is necessary to repair the voltage drop at the end of the received voltage can be done by raising the voltage of the tip tell .. To solve the voltage drop voltage regulator can be used on condition that the nominal voltage of 20 kV medium voltage distribution (phases) or 11.57 kV (-phase neutral) phase-neutral .Batas minimal service = -10% of nominal voltage = 10.41 kV or at 18 kV (phases). Limit the maximum phase-neutral service = + 5% of nominal voltage = 12.15 kV or at 21 kV (phases). The voltage phases of minimal services selected as the basis for calculation was 18.5 KV (= - 7.5% x the nominal voltage). The ability of raising and lowering the voltage regulator at the point of = ± 10% (10% raise and a 10% lower). From the research data is the output voltage at the feeder each - each 10.4 to 27.25% that do not meet the delivery via a substation. After passing through the generator voltage regulator's voltage fall below 5% eligible for dispply from substations to consumers